A novel immune checkpoint siglec-15 antibody inhibits LUAD by modulating mφ polarization in TME - Xuejun Xiao; Yan Peng; Zheyue Wang; Louqian Zhang; Tingting Yang; Yangyang Sun; Yufeng Chen; Wenqing Zhang; Xinxia Chang; Wen Huang; Shuning Tian; Zhenqing Feng; et al. (Elsevier, 2022)
Background: Siglec-15 (S15) is a type-I transmembrane protein and is considered a new candidate of immune checkpoint inhibitor for cancer immunotherapy. Methods: In the present study, we first constructed and characterized a chimeric S15-specific monoclonal antibody (S15-4E6A). Then, the antitumor effectiveness and modulatory role of S15-4E6A in macrophages (mφs) were explored in vitro and in vivo. Finally, the underlying mechanism by which S15mAb inhibits LUAD was preliminarily explored. Results: The results demonstrated the successful construction of S15-4E6A, and S15-4E6A exerted an efficacious tumor-inhibitory effect on LUAD cells and xenografts. S15-4E6A could promote M1-mφ polarization while inhibiting M2-mφ polarization, both in vitro and in vivo. Conclusions: S15-based immunotherapy that functions by modulating mφ polarization may be a promising strategy for the treatment of S15-positive LUAD.